Mama goat and her kids - Haq, Roohi (Karachi : Paramount books, 2017)
"Mama Goat and her Kids" likely tells a heartwarming story about a mother goat and her children. The cover suggests a vibrant, outdoor setting, possibly with some animal friends nearby. The narrative probably focuses on the love, care, and adventures shared within this goat family.
Location: 3B.
Keywords: Story book